Hepatic Transcriptomic Patterns in the Neonatal Rat After Pentabromodiphenyl Ether Exposure. (February 2020) - Dunnick, June K.; Shockley, Keith R.; Morgan, Daniel L.; Travlos, Gregory S.; Gerrish, Kevin; Ton, Thai-Vu T.; Wilson, Ralph; Brar, Sukhdev S.; Brix, Amy E.; Waidyanatha, Suramya; Mutlu, Esra; Pandiri, Arun Kumar R.
Human exposure to pentabromodiphenyl ether (PBDE) mixture (DE-71) and its PBDE-47 congener can occur both in utero and during lactation. Here, we tested the hypothesis that PBDE-induced neonatal hepatic transcriptomic alterations in Wistar Han rat pups can inform on potential toxicity and carcinogenicity after longer term PBDE exposures. Wistar Han rat dams were exposed to either DE-71 or PBDE-47 daily from gestation day (GD 6) through postnatal day 4 (PND 4). Total plasma thyroxine (T4) was decreased in PND 4 pups. In liver, transcripts for CYPs and conjugation enzymes, Nrf2, and ABC transporters were upregulated. In general, the hepatic transcriptomic alterations after exposure to DE-71 or PBDE-47 were similar and provided early indicators of oxidative stress and metabolic alterations, key characteristics of toxicity processes. The transcriptional benchmark dose lower confidence limits of the most sensitive biological processes were lower for PBDE-47 than for the PBDE mixture. Neonatal rat liver transcriptomic data provide early indicators on molecular pathway alterations that may lead to toxicity and/or carcinogenicity if the exposures continue for longer durations. These early toxicogenomic indicators may be used to help prioritize chemicals for a more complete toxicity and cancer risk evaluation.